Implementation of Mathematics Learning Through Media Arrange Smart Dice to Improve Counting Ability in Early Childhood - Nofriyanti, Yelva; Sari, Heni Meila (Program Studi Magister Pendidikan Anak Usia Dini, 2019)
The implementation of mathematics learning in some kindergartens in the city of Padang has not developed optimally. While in Rahmah Abadi Kindergarten that learning mathematics, especially numeracy has been well developed. The purpose of this study was to describe the implementation of mathematical learning using smart dice media for children's numeracy in Rahmah Abadi Kindergarten. The research method used was descriptive approach qualitative. Data collection techniques used are observation, interviews, and documentation. The re-sults showed that the implementation of mathematics learning using smart dice stacking media in kindergarten Rahmah Abadi was a child who was able to recognize numbers, count numbers 1-10 and simple summation. Keywords: Media Arrange Smart Dice, Counting Ability References Arikunto, S. (2014). Prosedur Penelitian. Jakarta: Rineka Cipta. Azhar Arsyad. (2013). Media Pembelajaran. Jakarta: Rajawali. Bowman, B. T., Donovan, M. S., & Burns, M. S. (2001). Eager to Learn. Eager to Learn. Washington DC: NAtional Academy Press. https://doi.org/10.17226/9745 Darmadi, H. (2014). Metode Penelitian Pendidikan Sosial. Bandung: Alfabeta. E Sovia. (2015). Buat Anak Anda Jago Eksakta (Rahasia Membuka Kecerdasan Eksakta Sejak Dini). Yogyakarta: Diva Press. Harris, B., & Petersen, D. (2017). Developing Math Skills in Early Childhood. Issue Brief. Mathematica Policy Research, Inc., (February), 1–6. Retrieved from http://ezproxy.library.uvic.ca/login?url=http://search.ebscohost.com/login.aspx?direct=true&db=eric&AN=ED587415&site=ehost-live&scope=site Kustandi. (2013). Media Pembelajaran Manual dan Digital. Jakarta: Ghalia Indonesia. Mashar, R. (2011). Emosional Anak Usia Dini dan Strategi Pengembangannya. Jakarta: Kencana. Mulyani, N. (2016). Dasar-dasar Pendidikan Anak Usia Dini. Yogyakarta: Kalimedia. Newzealand, G. (2013). Number: Early Learning Progression. Oktriyani, N. (2017). Peningkatan Kemampuan Berhitung Anak Usia Dini Melalui Permainan Lingkaran Angka Di Taman Kanak-Kanak Qatrinnada Kecamatan Koto Tangah Padang. Lectura: Jurnal Pendidikan Anak Usia Dini, 1(1), 82-96. Rohmah, N., & Waluyo, E. (2014). Arithmetic Dice Media as Counting Concept Introduction Media in Early Childhood Setting. Indonesian Journal of Early Childhood, 3(2), 127–133. https://doi.org/10.15294/ijeces.v3i2.9486 Rutherford, K. (2015). Why Play Math Games? US. Smith, S. S. (2009). Early Childhood Mathematics. USA: Pearson. Sudarna. (2014). Pendidikan Anak Usia Dini Berkarakter. Jakarta: Perpustakaan Nasional RI. Sugiyono. (2016). MetodePenelitianPendidikan:PendekatanKuantitatif,Kualitatif, dan R&D. Bandung: Alfabeta. Sujiono, Y. N. (2008). Metode Pengembangan Kognitif. Jakarta: Universitas Terbuka. Suryana, D. (2013). Pendidikan Anak Usia Dini (teori dan praktik pembelajaran). Padang: UNP Press. Susanto, A. (2017). Pendidikan Anak Usia Dini (Konsep dan Teori). Jakarta: Bumi Aksara. Suyanto, S. (2003). Konsep Dasar Pendidikan Anak Usia Dini. Yogyakarta: UNY Press. Trianto. (2011). Desain Pengembangan Pembelajaran Tematik Bagi Anak Usia Dini TK/RA & Anak kelas awal SD/MI. Jakarta: Kencana Prenada Media Group. Triharso, A. (2013). Permainan Kreatif dan Edukatif untuk Anak Usia Dini. Jakarta: Gaung Persada Press Group. Ulfah., S. dan M. (2013). Konsep Dasar PAUD. Bandung: PT Remaja Rosdakarya.